Vitamin D and skeletal muscle regeneration: A systems approach - Owens, D. J.; Sharples, A. P.; Donovan, T.; Tang, J.; Fraser, W. D.; Morton, J. P.; Stewart, C. E.; Close, G. L. (Japanese Journal of Physical Fitness and Sports Medicine, 2016)
Taken together, these human data are the first to demonstrate that Vitamin D3 is important for muscle regeneration in vivo and provide potential mechanisms for this observation in vitro. The findings are particularly pertinent given the high prevalence of low serum 25[OH]D worldwide and imply that maintaining optimal serum 25[OH]D concentration may benefit muscle remodelling across the lifespan.